The apparent variability of silkworm (Bombyx mori) silk and its relationship with degumming. (May 2016) - Perea, Gracia Belén; Solanas, Concepción; Marí-Buyé, Núria; Madurga, Rodrigo; Agulló-Rueda, Fernando; Muinelo, Alfonso; Riekel, Christian; Burghammer, Manfred; Jorge, Inmaculada; Vázquez, Jesús; Plaza, Gustavo R.; Torres, Adriana L.; et al.
Graphical abstract: Variation induced in the tensile properties of silkworm ( Bombyx mori ) silk fibers by degumming includes the appearance of a characteristic two-yield points stress-strain curve. Highlights: The variability of silkworm silk is an artifact that results from the degumming treatment. Exposure to water and high temperature rearranges the hydrogen bond network of silk. Rearrangement of the hydrogen bonds induces conformational changes and increases crystallinity. As spun fibers are stiffer than treated ones, despite their lower crystallinity. Silk can be described with a shear lag model taking into account variation in hydrogen bonding. Abstract: As spun silkworm ( Bombyx mori ) silk fibers were compared in terms of their tensile behavior and microstructure with fibers subjected to different degumming treatments. Fibers were initially retrieved by forced silking directly from the worms and, either characterized in the as spun condition, or subjected to one of the following treatments: immersion in water, conventional degumming or degumming under longitudinally constrained conditions. Microstructure was assessed by X-ray diffraction and Raman spectroscopy. In addition, polyacrylamide gel electrophoresis was used to determine the influence of degumming on silk at a molecular level. Our study not only shows that degumming represents a major contribution to the accepted idea of silkworm silk as a highly variable material, but also provides new insights in the relationship between microstructure and tensile behavior in these fibers. In particular, it is shown that the arrangement of the hydrogen bond network in fibers subjected to different treatments plays a critical role in determining the mechanical behavior of silkworm silk.